IMPLEMENTASI AYAT – AYAT ASURANSI SYARI’AH PADA PRODUK TAFAKULLI SALAM - Vida Rofika Miladiah (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2022)
The development of conventional insurance becomes a significant discussion, because there is a ban in Islam, then the creation of Sharia insurance as one of the solutions of the ribawi economic system. Over time the development of sharia insurance industry in Indonesia named PT. Takaful Indonesia Company (STI). With the existence of tafakul insurance will provide assistance and protection among a number through investments in the form of assets or tabarru' which provides a pattern of development to deal with certain risks through the Shari'ah agreement. There are several verses of the Qur'an and hadith that discuss sharia insurance. In the Qur'an each qur'anic letter has a different meaning than other letters. However, between letters with each other has a relationship because it has the same theme discussion. This paper aims to discuss how the implementation of sharia insurance verses in the Qur'an regarding tafakulli products by performing thematic interpretations. The analysis method used is descriptive analysis using the maudhu'I or thematic approach. The results of the discussion showed that insurance has two laws, the first of which is haram because it contains the element riba (surah QS. Hud 11: 6, an-Naml 27:64, al-Hijr 15), the second is permissible because there is a helpful nature (Ta'awun) and free from vile qualities (which are hated by Allah) (QS Al Maidah verse: 2). Ta'awun is a concept of help found in Islam, Ta'awun itself is one of the concepts of insurance listed in (QS Al Maidah verse: 2). Keywords: Implementation; Sharia Insurance; Thematic Interpretation